Copper-catalyzed regioselective C-H alkylation of phenol derivatives with unactivated alkyl chlorides: manifesting a Cu(I)/Cu(III) pathway - Verma, Suryadev K.; Punji, Benudhar (Journal of Catalysis, 2024)
The use of unactivated alkyl chlorides in regioselective C -H alkylation is a highly challenging process with diverse applications of alkylation strategy in drug discovery and agrochemistry. In this work, we report an efficient and cost-effective copper -catalyzed protocol for the coupling of unactivated alkyl chlorides with the C -H bond of phenol derivatives via 2-pyridinyl chelation assistance. The reaction shows a high level of regioselectivity, leading to an exclusive ortho alkylation and providing a broad scope with the endurance of numerous functionalities such as silyl, ether, thioether, pyrrolyl, indolyl, carbazolyl groups, including alkyl bearing fatty alcohol, nonylphenol, and vitamin E. Detailed mechanistic investigations suggest that the alkylation occurs through a two -electron oxidative addition of alkyl chloride to an active Cu(I) species. Deuterium labeling and kinetics experiments indicate a facile and reversible C -H bond activation process. Overall, the alkylation follows a Cu(I)/Cu(III) pathway involving chelation-assisted smooth C -H metalation and rate -limiting C-Cl oxidative addition of alkyl chloride.